Higher SBP in female patients with mitochondrial disease. Issue 5 (7th February 2022) - Viering, Daan H.H.M.; van Borselen, Marjolein D.; Deinum, Jaap; Bindels, Rene J.M.; de Baaij, Jeroen H.F.; Janssen, Mirian C.H.
Abstract : Background: Previous research suggests that hypertension is more prevalent among patients with mitochondrial diseases. Blood pressure (BP) is linearly related to increased cardiovascular risk, and this relationship is strongest for SBP; nevertheless, studies on SBP and DBP in mitochondrial diseases have not yet been performed. Method: In a retrospective case–control study design, BP in mitochondrial disease patients was compared with BP in a population cohort. Secondly, using multiple linear regression, we examined blood pressure differences in various genetic mitochondrial diseases. Lastly, we explored additional predictors of BP in a subgroup with the m.3243A > G variant. Results: Two hundred and eighty-six genetically confirmed mitochondrial disease patients were included. One hundred and eighty of these patients carried the m.3243A>G mitochondrial DNA variant. SBP was 9 mmHg higher in female mitochondrial disease patients than in the general female population (95% CI: 4.4–13.3 mmHg, P < 0.001), whereas male patients had similar BP compared with controls. BP was not significantly different in patients with m.8344A>G and m.8363G>A, a mtDNA deletion or a nuclear mutation compared with m.3243A>G patients. Higher SBP was a predictor for left ventricular hypertrophy in the m.3243A>G subgroup ( P = 0.04). Conclusion: Novel aspects of the role of mitochondrial dysfunction in blood pressure regulation are exposed in this study. Compared with the general population, female mitochondrial disease patients have a higher SBP. Left ventricular hypertrophy is more prevalent in patients with higher SBP. Clinicians should be aware of this to prevent hypertensive complications in mitochondrial disease patients.